Cyberthreats as a Component of Threats in the Contemporary World (a Legal Aspect) - Bezzubov, Dmytro; Ihonin, Ruslan; Diorditsa, Ihor (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).04, 2017)
In their paper, the authors studied legal understanding of cyber threats in the contemporary world. The emphasis was placed on the fact thatthere is no definition of ʽcyber threatsʼ at both the international and domestic levels, which leads to adverse consequences. The authors suggested their own perception of ʽa cyber threatʼ – illegal punishable acts of subjects of information legal relations that create a danger to vital interests of man, society and the state as a whole, fulfillment of which depends on proper operation of information, telecommunication and information telecommunication systems, as well as to relations associated with information production, collection, acquisition, storage, use, dissemination, protection, and security. It is stated that the essence of cyber threatsconsists in their sources, that is, in subjects of information legal relations, while information is their direct target. Information interventions pose a major threat to cybersecurity. It was noted that threats can be both internal and external. To develop an effective mechanism able to counter cyber threatsto Ukraine, it is suggested taking current practices of foreign countries and the international community as a model and bringing them in line with the Ukrainian realities.